Engineering Geological Assessment for Rock Slope Stability of Chosen Areas from SW of Haibat Sultan Mountain, Kalkasmak-Koisanjaq Road / Iraq - Al-Samarrai, Thair Thamer (Iraqi Journal of Science, 2022)
Engineering geological study of rock slope stability in two stations lying in the SW of Haibat Sultan mountain, along the Kalksmaq - Koisanjaq road was carried out. At each station, rock slopes and discontinuities were comprehensively surveyed and the relationships with failures were determined. The limestone rock was described in engineering terms, the types of failures recorded during field study were rock roll and toppling whiles the probable failures were sliding, toppling, and rock roll. The study also revealed that the factors affecting slope stability in the study area were slope angle, height, dip of strata, and discontinuities (which are almost perpendicular to the bedding plane). The laboratory test, of the rock samples (point-load test) showed that the average value of compressive strength of the rock for the study area is about 192 M.Pa. Landslide possibility index (LPI) classification of Bejerman (1998) is applied to the study area, it shows that slopes of both stations lie in the category IV of moderate (LPI). The hazards related to the (LPI) are also moderated (LPI). Some remedial measures were suggested to slopes, such as remove of unstable blocks, to avoid further failure problems and safeguard the slopes in the future.